KONSEP HARMONI MUSIK GUSTAV STRUBE DAN KONSEP KEHARMONISAN DALAM ETIKA KEHIDUPAN - Alex Richsyon Nunumete (IAKN Ambon, 2022)
Harmony is a method of maintaining balance because of differences. The concept of harmony is very inherent in various aspects of human life, harmony in social life, harmony in religious life, culture, even the concept of harmony is also used in music to maintain the balance of sounds that are sounded together and have their own concepts. One of the concepts in musical harmony was built by Gustav Strube based on his experience in designing musical compositions. Gustav Strube's concept of harmony is then equated with the concept of harmony in the ethics of life. The method used in this research is descriptive qualitative method, namely the data collected in the form of words, pictures and in the research to be carried out, the researcher wants to describe the ethics that are still enforced by community groups. The facts that need to be examined are the theory of musical harmony and the facts about the harmony created by the ethics of life. Data analysis was carried out by collecting literature data and then discussing the concept of harmony by Gustav Strube and the concept of life ethics to live in harmony.